Survei Dampak Penggunaan Integrasi Berkelanjutan dalam Perusahaan Pengembangan Perangkat Lunak - Kharisma Monika Dian Pertiwi; Ana Tsalitsatun Ni’mah; Siti Rochimah (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
Continuous Integration (CI) is a software development technique adopted from the agile method. CI is widely used by software development companies, so there is a need for research to determine the impact of using CI in the software development industry. This study aims to analyze the impact of the use of CI on software and software development companies that are being developed. This research applies the Systematic Literature Review (SLR) research method. This study has two Research Questions, namely RQ, (1) “What is the impact of using Continuous Integration in software development?” (2) “What is the effect of using Continuous Integration on the company?”. The impact of the use of CI was identified by conducting a literature search for CI which was published in 2012 until 2018. Literature search was conducted on the IEEE Xplore and Science Direct. From the search, a total of 6,514 literature regarding CI is found. Then, a screening process is carried out based on inclusion criteria, exclusion criteria, and quality assessment of literature. After screening, 14 literature were selected. The selected literature met the specified criteria and could represent to determine the impact of using CI. Out of the 14 selected literatures, 13 literatures were able to answer the two research questions. Based on the SLRs that have been done, it is shown that the use of CI in software development can have good and bad effects on software and software development companies.